Islamic Education Management as Educational Governance: Revisiting Classical Organization Theory through Epistemic and Institutional Reconstruction - Oky Trisna Sanjaya; Hasnida (Kartika: Jurnal Studi Keislaman, 2026)
Classical organizational theory represents an early systematic framework for understanding structure, authority, and managerial practices. Rooted in the industrial era, its core principlesrationality, hierarchy, specialization, and controlcontinue to influence organizational governance today. However, existing studies tend to focus on comparing classical theory with modern paradigms, with limited attention to how its assumptions persist and adapt within contemporary, value-laden organizational contexts, including educational institutions.This article presents a conceptual review that reexamines the contributions of classical thinkers and evaluates their continued relevance through a synthesis with modern theoretical developments. The analysis reveals both continuity and limitations, particularly in explaining informal dynamics and ethical complexity. Nevertheless, classical theory remains essential as a conceptual foundation for understanding authority, accountability, and institutional coherence.Thus, it serves as a reflective basis for analyzing educational governance, especially within the context of Islamic Educational Management, which is oriented toward values and knowledge